2017
DOI: 10.1177/1748048517747493
|View full text |Cite
|
Sign up to set email alerts
|

Newspaper portrayal of Chinese outward foreign direct investment in Latin American newspapers: A content analysis

Abstract: The current study is a content analysis of international economic news about Chinese outward foreign direct investment in Latin American countries from corresponding Latin American newspapers. We studied the portrayal of Chinese outward foreign direct investment among 14 different Latin American newspapers. The study aims at illustrating differences between newspaper portrayals of Chinese outward foreign direct investment in the region, with a special focus on the possible factors that influence the editorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Examining five news outlets from Colombia, Peru, Mexico, El Salvador and the Dominican Republic, Ospina Estupinan (2017) revealed how China's image is often negative in Spanish-speaking countries. Zhu and Wang (2018) focused on how Chinese outward foreign direct investment is portrayed in 14 newspapers across eight countries, including Argentina, Brazil, Chile, Colombia, Mexico, Panama, Peru and Venezuela. With this paper, we contribute to the understanding of China's image in Brazil, by examining news co-production between media organisations from both countries.…”
Section: Methodsmentioning
confidence: 99%
“…Examining five news outlets from Colombia, Peru, Mexico, El Salvador and the Dominican Republic, Ospina Estupinan (2017) revealed how China's image is often negative in Spanish-speaking countries. Zhu and Wang (2018) focused on how Chinese outward foreign direct investment is portrayed in 14 newspapers across eight countries, including Argentina, Brazil, Chile, Colombia, Mexico, Panama, Peru and Venezuela. With this paper, we contribute to the understanding of China's image in Brazil, by examining news co-production between media organisations from both countries.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, coverage on this topic in newspapers in other countries tended to be more negative (e.g., Argentina, Colombia) or neutral (e.g., Brazil, Mexico). Zhu & Wang (2018) also found that national differences influenced the differences in journalistic tone rather than the political stances of the newspapers analyzed. In addition, their content analysis shows that both mainstream outlets El Mercurio and La Tercera favored economic consequences over conflicts in their coverage of Chinese investments in Latin America and that the consequences of these investments were mostly portrayed as mutually beneficial.…”
Section: Narratives In Public Diplomacy: China and Its Presence In Chilementioning
confidence: 95%
“…Furthermore, many have argued that Chile is an interesting case study for understanding the Chinese geopolitical and economic strategy towards Latin America (Gachúz, 2012) since Chile may work as a demonstration of Beijing's benign influence in the region (Labarca, 2013). While this article focuses on elites as political actors and not on the state, following Zhu and Wang (2018), we believe that the examination of editorials and opinion columns allows for the understanding of the attitudes of a country's elite class and/or government towards Chinese presence in the region.…”
Section: Narratives In Public Diplomacy: China and Its Presence In Chilementioning
confidence: 98%
“…Cardenal (2017) explains that negative environmental aspects of China's economic projects in Peru have been played down or suppressed in the Peruvian news media. On the other hand, the frames of “conflict” and “economic consequences” were also found in stories about Chinese investments in Latin America (Zhu and Wang, 2018). Most news flow studies have focused on news agencies or media sources (at the macro-level).…”
Section: Mediated China In Latin Americamentioning
confidence: 99%